ChemInform Abstract: An Environment‐Friendly Synthesis of 2, 3‐Disubstituted‐2‐iminothiazoline‐4‐ones. Issue 31 (14th July 2016) - Meng, Ge; Zheng, Meilin; Dong, Mengshu; Wang, Mei; Zheng, Aqun; Guo, Zengjun
Abstract: [starting from aromatic or aliphatic substituted iminothiazolines by an improved method including an auto‐catalyzed reaction.]